Holiday effect di Bursa Efek Indonesia, di Bursa Efek Amerika dan di Bursa Efek Jepang sebelum, sesaat dan sesudah pandemi covid-19 - Apriani, Suci Selia; Komariah, Siti (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The phenomenon of traders entering the capital market is one of the causes of the stock market becoming unstable and experiencing market inefficiencies, which are often known as "market anomalies." The holiday effect is a market anomaly phenomenon that shows a tendency for the rate of return on a day before a holiday, but it can also be higher than the rate of return on other ordinary days. This study aims to find out how the holiday effect phenomenon is affecting the Indonesian, American, and Japanese stock exchanges during the 2019–2021 period. In addition to knowing whether there is a difference in stock returns between the day before the holiday and other days, you also need to know whether there is a difference in stock returns between the day before the holiday on the Indonesian, American, and Japanese stock exchanges during the study period. The data used is daily index data for the period January 2019 to December 2021 for each country. The research methods used are comparative methods and event studies. While the normality test, homogeneity test, ANOVA test, post hoc test, and independent sample t-test are used for technical analysis. The results showed that there was no holiday effect on the Indonesian, American, and Japanese stock exchanges because there was no significant difference in the average stock return between the day before the holiday and other days.